Students' Mathematical Abstractive Reflective Thinking Ability Through Contextual Learning - Akhmad Nurul Mutamam; Wati Susilawati; Iyon Maryono; Ida Nuraida (Gunung Djati Conference Series, 2022)
Deductive-axiomatic mathematical objects lead to low mathematical ability of students. Therefore, this study aims to examine students' mathematical contextual abstractive abilities. Case studies are used in this research using literature studies. The case in this study is the weak mathematical reflective ability of students who are used to find out the factors that cause the low mathematical reflective ability of students. The results showed that there was still a low ability to think abstractly and contextually mathematically because they were not used to the previous level and lack of experience